(untitled) (Eternitas: Jurnal Teknik Sipil, 2023)
Earthquakes are natural phenomena that can cause building collapse and loss of life. During an earthquake, buildings standing on the ground will experience movement at its base, the acceleration arising from ground motion will cause horizontal / lateral inertial forces on the mass of the structure, then used as a plan earthquake force that must be reviewed in planning. According to article 7.8 of SNI 1726:2019, the seismic base shear force is the product of the seismic response coefficient (Cs) and the building’s seismic weight (W). The seismic response coefficient must be determined by the spectral acceleration parameter (SDS) which is highly dependent on the site class classification regulated in Article 5 of SNI 1726:2019, which uses the top 30 m layer profile data from the soil investigation. This study uses a 1-span reinforced concrete frame with 3 floors and 20 locations spread across Kupang City to see the effect of site class on the magnitude of seismic base shear force. The results showed that the base shear force of SC site increased by 87.5% against SB site, the base shear force of SD site increased by 9.22% against SC then the shear force of SE site decreased by 1.94%..